The impact of harmonious parent-child relationships on the development of psychological well-being and personality resilience: a qualitative study in healthcare professionals - Spytska, Liana (2024)
Introduction: The relationship between parents and children is the foundation of family life, which determines the mental and emotional well-being of each family member. Therefore, understanding the impact of harmonious relationships on personal development is important and relevant to society, as it can have far-reaching consequences for the quality of life. Objective: The purpose of this study was to investigate how harmonious relationships between parents and children affect the child’s mental health, specifically from the perspective of healthcare workers. Method: Qualitative and quantitative methods, including systematization, synthesis, analysis, and interviews, were employed in the study. Data were collected through interviews with parents and children, as well as through an analysis of scientific literature and clinical cases. Result: It was found that close relationships between parents and children play a key role in the development of adolescents’ self-esteem. The quality of these relationships is determined by mutual understanding, support, and trust. Interaction with parents contributes to the psychological growth and positive self-image of children. It was also found that having free time with parents contributes to a more profound emotional connection and understanding. The study confirmed the importance of harmonious parent-child relationships for the mental well-being of children. The results of an interview with 100 mental health professionals confirmed the effectiveness of strategies such as emotional support, joint activities, setting clear boundaries, and others in establishing positive relationships between parents and children. The study found that family therapy, play therapy, cognitive behavioural therapy (CBT), and parental psychological education are effective methods for stimulating harmonious relationships between parents and children. Conclusion: These approaches promote the child’s mental well-being and contribute to a better understanding of their needs and emotions. The findings can be used to develop and implement intervention and support programmes for parents to improve their relationships with their children.